PENGARUH ASET PAJAK TANGGUHAN, BEBAN PAJAK TANGGUHAN, BEBAN PAJAK KINI, PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2017) - Inten, Nestiti Gemi; Vince, Ratnawati; Susilatri, Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study was aimed to investigate the effect of deferred tax asset,deferred tax expense, current tax expense, and tax planning on earningsmanagement. The population of this study are manufacture companies listed onthe Indonesia Stock Exchange, from 2014 to 2017. The samples of this study areall companies were selected by purposive sampling method. This study usedlogistic regression analysis to test whether the independent variables affect thedependent variable. The results showed that deferred tax asset and current taxexpense respectively had a significant effect on earnings management inmanufacturing companies during the period 2014 to 2017, while deferred taxexpense and tax planning did not affect the earnings management. Value ofNagelkerke R Square is 0.337, which means that the variability of the dependentvariable can be explained by the independent variable as 33,7%, while theremaining variables 66,3% are explained variability of other variables outsidethis model study.Keywords : Deferred Tax Asset, Deferred Tax Expense, Current Tax Expense,Tax Planning, Earnings Management.